From east to west. Enlargement and migration flows - Ferrero, Ruth (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
The end of the Cold produced migratory flows of an economic type in the direction East-West Although the exchange and movement of populations in Europe is nothing new, what was new was the change in the underlying philosophy. The change of paradigm from a world with two opposing poles to one with an hegemonic power, shattered all the schemes that until then were taken for granted. Since the fall of the Berlin wall the issue was no longer to take in political refugies coming from the soviet block, butrather to regulate the flows coming from those countries in more and more numbers. In this paper we try to reconstruct the history of the development of control of the migratory flows coming from Central and Easter Europe towards the European Union before,during and after the enlowgement processes which have taken place in 2004 and 2007.
Keywords: Migration flows; Central and Eastern Europe; European Union